Toxicity of internal mammary irradiation in breast cancer. Are concerns still justified in times of modern treatment techniques?. (2nd October 2020) - Borm, Kai Joachim; Simonetto, Cristoforo; Kundrát, Pavel; Eidemüller, Markus; Oechsner, Markus; Düsberg, Mathias; Combs, Stephanie Elisabeth
Abstract: Background: The purpose of this study was to estimate the additional risk of side effects attributed to internal mammary node irradiation (IMNI) as part of regional lymph node irradiation (RNI) in breast cancer patients and to compare it with estimated overall survival (OS) benefit from IMNI. Material and methods: Treatment plans ( n = 80) with volumetric modulated arc therapy (VMAT) were calculated for 20 patients (4 plans per patient) with left-sided breast cancer from the prospective GATTUM trial in free breathing (FB) and in deep inspiration breath hold (DIBH). We assessed doses to organs at risk ((OARs) lung, contralateral breast and heart) during RNI with and without additional IMNI. Based on the OAR doses, the additional absolute risks of 10-year cardiac mortality, pneumonitis, and secondary lung and breast cancer were estimated using normal tissue complication probability (NTCP) and risk models assuming different age and risk levels. Results: IMNI notably increased the mean OAR doses. The mean heart dose increased upon IMNI by 0.2–3.4 Gy (median: 1.9 Gy) in FB and 0.0–1.5 Gy (median 0.4 Gy) in DIBH. However, the estimated absolute additional 10-year cardiac mortality caused by IMNI was <0.5% for all patients studied except 70-year-old high risk patients (0.2–2.4% in FB and 0.0–1.1% in DIBH). In comparison to this, the published oncological benefit of IMNI ranges between 3.3% and 4.7%. The estimated additional 10-year risk of secondary cancer of the lung or contralateral breast ranged from 0–1.5% and 0–2.8%, respectively, depending on age and risk levels. IMNI increased the pneumonitis risk in all groups (0–2.2%). Conclusion: According to our analyses, the published oncological benefit of IMNI outweighs the estimated risk of cardiac mortality even in case of (e.g., cardiac) risk factors during VMAT. The estimated risk of secondary cancer or pneumonitis attributed to IMNI is low. DIBH reduces the estimated additional risk of IMNI even further and should be strongly considered especially in patients with a high baseline risk.